Communicating the right emotion makes violence seem less wrong: Power-congruent emotions lead outsiders to legitimize violence of powerless and powerful groups in intractable conflict. (May 2014) - Kamans, Elanor; van Zomeren, Martijn; Gordijn, Ernestine H.; Postmes, Tom
In intractable intergroup conflicts, groups often try to frame intergroup violence as legitimate through the use of emotional appeals. Two experiments demonstrate that outsiders' perception of which emotion conflict parties communicate influences the extent to which they legitimize their violence. Results show that although outsiders typically give more leeway to powerless groups because of their "underdog" status, communicating power-congruent emotions qualifies this effect; observers legitimize intergroup violence most when powerless groups communicate fear and when powerful groups communicate anger . This is because fear communicates that the group is a victim that cannot be blamed for their violence, whereas anger communicates that the group is wronged and thus their violence seems righteous and moral. Results further show that sympathy for the powerless appears to be a more fragile basis for legitimization of violence than the moral high ground for the powerful. We discuss the theoretical and practical implications of these findings.